Motion vision : design of compact motion sensing solutions for autonomous systems navigation - Kolodko, Julian (IEE control engineering series ;, 2005)
This comprehensive new book deals with motion estimation for autonomous systems from a biological, algorithmic and digital perspective. An algorithm, which is based on the optical flow constraint equation, is described in detail. This algorithm fits with the motion processing model, hardware and software constraints and resolves depth-velocity ambiguity, which is critical for autonomous navigation. There is also extensive coverage on the use of this algorithm in digital hardware and describes both the initial motion processing model, the chosen hardware platforms, and the global function of th.